The Abuse of Right in Constitutional Law: Problem Statement - A. I. Evstafyev (Теоретическая и прикладная юриспруденция)
Abuse of law is generally considered to be a legal phenomenon most inherent to private law. Historically, it first appeared in private Roman law; it found doctrinal development and application in legal sciences associated with private law. This issue and even the possibility of its existence are not paid due attention in constitutional legal regulation and the science of constitutional law. This article attempts to substantiate the existence of abuse of rights (powers) in the spheres that were mentioned, and to identify the problem of the insufficiency of appropriate legal regulation, which gives rise to the preconditions for abuse of rights. The current paper highlights distinctive elements of the legal phenomenon under study, and also gives a definition and assessment to the “gray zone” in which abuse of law in constitutional and legal relations is possible.